Control of pendulum oscillations by Tuned Liquid Dampers. (October 2022) - Furtmüller, Thomas; Joas, Gregor; Adam, Christoph
Abstract: This paper is concerned with passive vibration control of pendulum-type structures. Specifically, low-frequency vibrations are addressed, such as those occurring in ropeway passenger cabin oscillations. Since low frequency vibration control devices are advantageously realized by liquid absorbers, a Tuned Liquid Damper is considered here. Equations of motions for a planar mechanical model of a mathematical pendulum are derived for the two-degree-of-freedom system composed of the pendulum and the fundamental sloshing mode of the liquid. The derived mathematical models are validated by experimental investigations. To mitigate wave breaking phenomena in the sloshing liquid, a so-called floating roof proposed in literature is implemented in the experimental models. It is shown that passive control by means of the Tuned Liquid Damper is as efficient as a Tuned Mass Damper with the same mass, provided that the nonlinear damping behavior of the liquid is properly taken into account in the design of the sloshing damper.